Conceptual design conceptual scheme optimization based on integrated design objectives. (September 2018) - Jiang, Shaofei; Jing, Liting; Peng, Xiang; Chai, Hao; Li, Jiquan
In the early conceptual design process, a large number of conceptual schemes can be selected. However, existing studies primarily focused on mapping from the function to the principle solution and then evaluating the principle scheme. Currently, many concept selection methods are used for a small number of feasible schemes, thus not addressing a large number of initial conceptual schemes. As the scheme design is objective oriented, a reasonable design objective constraint should be considered when optimizing many schemes to avoid conflict between the conceptual scheme and the design objectives. This approach can quickly eliminate many unreasonable schemes produced by the principle of free combination. To address this problem, we propose a method for optimizing the conceptual design scheme based on integrated design objectives. First, the product design objectives and sub-objectives are obtained based on the functional requirements. A user requirement matrix is then created to cluster and analyse the sub-objectives. Second, a cooperative game model is created to coordinate sub-objective contradictions. Then, the game player and the strategy set are defined via secondary clustering, and the strategy utility is calculated to create a game utility matrix for each objective. Finally, the eigenfunction is analysed to obtain the strategy set satisfying the maximum requirement interest, which is applied in principle scheme optimization to quickly filter unreasonable schemes. The conceptual design of a transmission device is used as an example of the rapidly implemented optimization of the conceptual schemes.